Screening Mangrove Endophytic Fungi for Antimalarial Natural Products - Calcul, Laurent (MDPI, 2013)
We conducted a screening campaign to investigate fungi as a source for new antimalarial compounds. A subset of our fungal collection comprising Chinese mangrove endophytes provided over 5000 lipophilic extracts. We developed an accelerated discovery program based on small-scale cultivation for crude extract screening and a high-throughput malaria assay. Criteria for hits were developed and high priority hits were subjected to scale-up cultivation. Extracts from large scale cultivation were fractionated and these fractions subjected to both in vitro malaria and cytotoxicity screening. Criteria for advancing fractions to purification were developed, including the introduction of a selectivity index and by dereplication of known metabolites. From the Chinese mangrove endophytes, four new compounds (14–16, 18) were isolated including a new dimeric tetrahydroxanthone, dicerandrol D (14), which was found to display the most favorable bioactivity profile.